Highly self-ordered nanochannel TiO2 structures by anodization in a hot glycerol electrolyte - Lee, Kiyoung; Kim, Dam-Hee; Schmuki, Patrik (Chemical Communications, 2011)
In the present work, we report on the self-organized growth of TiO2 layers consisting of a highly aligned nanochannel morphology. We show that an electrochemical anodization process of Ti in a hot glycerol/K2HPO4 electrolyte can be adjusted to yield these self-organized TiO2 structures. The channel diameter and length are controllable by the anodization parameters. This directional structure can, for example, find application in dye-sensitized solar cells.
EAM Import::2019-03-13